2018
DOI: 10.1159/000491899
|View full text |Cite
|
Sign up to set email alerts
|

Function of SLC7A7 in T-Cell Acute Lymphoblastic Leukemia

Abstract: Background/Aims: Y+LAT1 protein, encoded by the SLC7A7 gene (a member of the SLC7 family), forms the cationic amino acid transport system y+L (system y+L). This system transports cationic amino acids such as arginine and lysine out of the cell. Arginine, in particular, is critical for T-cell activation and function in the immune response. Methods: We analyzed the role of the SLC7A7 gene in the cellular activities of Jurkat cells, specifically the cell cycle and cell proliferation, apoptosis, migration, and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Y+LAT1 protein, encoded by the SLC7A7 gene, forms the cationic amino acid transport system y+L, which transports cationic and large neutral amino acids from the cell to the extracellular space. Knockdown of SLC7A7 increased the cell apoptosis but decreased the G1 phase and cellular invasion in T-cell acute lymphoblastic leukemia [30].The common single nucleotide polymorphism (rs12436190) in SLC7A7 increases the risk of glioma in Chinese population [31]. Our study demonstrated that high SLC7A7 expression was associated with decreased OS and RFS in glioma patients.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Y+LAT1 protein, encoded by the SLC7A7 gene, forms the cationic amino acid transport system y+L, which transports cationic and large neutral amino acids from the cell to the extracellular space. Knockdown of SLC7A7 increased the cell apoptosis but decreased the G1 phase and cellular invasion in T-cell acute lymphoblastic leukemia [30].The common single nucleotide polymorphism (rs12436190) in SLC7A7 increases the risk of glioma in Chinese population [31]. Our study demonstrated that high SLC7A7 expression was associated with decreased OS and RFS in glioma patients.…”
Section: Discussionmentioning
confidence: 61%
“…SLC7A7 may also become promising druggable targets for LGG patients. Take SLC7A7 for example, inhibition of SLC7A7 expression increased the cell apoptosis, decreased the G1 phase and inhibited cell invasion in T-cell acute lymphoblastic leukemia [30].…”
Section: Discussionmentioning
confidence: 99%
“…SLC7A5 might cause different effects in different cell lines since it was reported that after knockdown of SLC7A5, cell cycle progression had been detected to be arrested at G1 phase in oral cancer [25], gastric cancer [26], and esophageal cancer [24,27]. Moreover, the cell number of G2 phase showed a signi cant increase while SLC7A5 was knockdown in T-cell acute lymphoblastic leukemia [48]. In the results of FACS, cell cycle was arrested in G1 phase after SLC7A5 knockdown obviously.…”
Section: Discussionmentioning
confidence: 97%
“…In NSCLC, SLC7A7 is a prognostic biomarker correlated with immune infiltrates ( Dai et al, 2021 ). For T cell acute lymphoblastic leukemia, SLC7A7 inhibits cell apoptosis and promotes cell migration and invasion ( Ji et al, 2018 ). Downregulation of SLC7A7 triggers an inflammatory phenotype in human macrophages and airway epithelial cells ( Rotoli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%